2010
DOI: 10.4149/neo_2010_01_035
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the GSTP1 promoter region in breast cancer is associated with prognostic clinicopathological parameters

Abstract: breast cancer, prognostic factors, hypermethylation, GSTP1, methylation-specific PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
1
11
2
Order By: Relevance
“…GSTP1 belongs to a family of metabolic enzymes and is involved in the detoxification of carcinogens and chemotherapeutic agents by conjugating them with glutathione [33]. In female breast cancer, GSTP1 hypermethylation is correlated with high-grade ductal carcinoma in situ and high-grade invasive breast cancer, presence of lymph node metastasis and poor outcome [4,30,34,35]. ER, encoded by ESR1 , is an important factor in breast cancer, because studies in females have shown that patients with hormone-negative tumors do not benefit from endocrine therapy [36].…”
Section: Discussionmentioning
confidence: 99%
“…GSTP1 belongs to a family of metabolic enzymes and is involved in the detoxification of carcinogens and chemotherapeutic agents by conjugating them with glutathione [33]. In female breast cancer, GSTP1 hypermethylation is correlated with high-grade ductal carcinoma in situ and high-grade invasive breast cancer, presence of lymph node metastasis and poor outcome [4,30,34,35]. ER, encoded by ESR1 , is an important factor in breast cancer, because studies in females have shown that patients with hormone-negative tumors do not benefit from endocrine therapy [36].…”
Section: Discussionmentioning
confidence: 99%
“…The seven classes of GSTs (a, m, p, s, q, k, z) have considerable substrate promiscuity, with different catalytic efficiencies (24,25). Most studies have focused on the various polymorphisms of the GSTs in breast cancer and drug resistance, although the resistance to various anticancer agents has also been linked to the overexpression of GSTs in tumor cells (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, integrated analysis showed GSTP1 and PALLD genes having low level gene expression as well as significantly higher methylation level of these gene promoters in luminal phenotype compared to the other two subtypes. Hypermethylation of the GSTP1 promoter has also been previously reported as having association with prognostic values [52], and repression of PALLD gene has been shown to contribute to invasive motility [53] and cancer cell migration [54]. Including these genes, a large number of detected genes from our analysis have overlapping of promoter regions with DHS region as well as polycom-associated H3K27me3 marked region, suggesting a potential interplay with gene transcription and that differential methylation may play important roles across the subtypes.…”
Section: Discussionmentioning
confidence: 99%